2019
DOI: 10.1146/annurev-arplant-050718-100114
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular View of Plant Local Adaptation: Incorporating Stress-Response Networks

Abstract: Ecological specialization in plants occurs primarily through local adaptation to different environments. Local adaptation is widely thought to result in costly fitness trade-offs that result in maladaptation to alternative environments. However, recent studies suggest that such trade-offs are not universal. Further, there is currently a limited understanding of the molecular mechanisms responsible for fitness trade-offs associated with adaptation. Here, we review the literature on stress responses in plants to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 195 publications
(119 reference statements)
1
74
0
Order By: Relevance
“…Among tree species with a wide range of morphology and growth potential, slow-growing species having a conservative resource-use strategy are least sensitive to drought [19], although the trade-off between drought tolerance and plant growth is not always significant [20]. Moreover, the C-S-R theory does not similarly employ to all abiotic stresses [21]. A trade-off between plant growth rate and cold hardiness, but not for drought, occurred among plants in 56 families of Douglas-fir [22].…”
Section: Introductionmentioning
confidence: 99%
“…Among tree species with a wide range of morphology and growth potential, slow-growing species having a conservative resource-use strategy are least sensitive to drought [19], although the trade-off between drought tolerance and plant growth is not always significant [20]. Moreover, the C-S-R theory does not similarly employ to all abiotic stresses [21]. A trade-off between plant growth rate and cold hardiness, but not for drought, occurred among plants in 56 families of Douglas-fir [22].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in their recent review on stress response networks in plant local adaptation, VanWallendael et al. () highlight that “integrating field‐based studies of local adaptation with mechanistic physiological and molecular biology promises advances in multiple areas of plant science.”…”
mentioning
confidence: 99%
“…One clear path toward linking sequence polymorphism to ecologically relevant traits, and ultimately to fitness, is to conduct detailed studies of the molecular and physiological mechanisms of adaptive traits in study systems for which local adaptation has already been demonstrated (Tonsor et al, 2005). Indeed, in their recent review on stress response networks in plant local adaptation, VanWallendael et al (2019) highlight that "integrating field-based studies of local adaptation with mechanistic physiological and molecular biology promises advances in multiple areas of plant science. "…”
mentioning
confidence: 99%
“…), rockcress (Boechera stricta), and monkeyflowers (Mimulus spp. ), where studies have revealed the genetic architecture and molecular basis of adaptive traits, including flowering time (Blackman et al, 2011), flowering phenology (Anderson et al, 2013), physiological adaptations to contrasting environments (Rieseberg et al, 2003) and drought resistance (Lowry & Willis, 2010;VanWallendael et al, 2019). In S. lautus, where multiple pairs of dune and headland populations have evolved repeatedly and independently along the Australian coast, genomic approaches are providing important insights into the genetic changes associated with rapid adaptive divergence.…”
Section: Genomics Of Adaptation and Parallel Evolutionmentioning
confidence: 99%